2013
DOI: 10.1177/1043454213513837
|View full text |Cite
|
Sign up to set email alerts
|

Living an Everyday Life Through a Child’s Cancer Trajectory

Abstract: The aim of this study was to illuminate the lived experiences of families where a child had survived 7 years from a diagnosis of childhood cancer. This article describes one part of an inductive and longitudinal research project that included 17 families. Four families whose child was diagnosed with cancer 7 years previously were interviewed using a hermeneutical phenomenological approach. The families lived experience was described in one essential theme, “Living an everyday life through the child’s cancer tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 24 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…Increased school absenteeism after completion of treatment has been described for survivors as well as siblings (French et al, 2013 ). The families have been described as still vulnerable and in need of support for up to 7 years after the diagnosis (Sundler et al, 2013 ). Adult siblings of childhood cancer survivors have reported an increased incidence of risky alcohol consumption, associated with symptoms of depression, anxiety, and psychiatric distress (Lown et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Increased school absenteeism after completion of treatment has been described for survivors as well as siblings (French et al, 2013 ). The families have been described as still vulnerable and in need of support for up to 7 years after the diagnosis (Sundler et al, 2013 ). Adult siblings of childhood cancer survivors have reported an increased incidence of risky alcohol consumption, associated with symptoms of depression, anxiety, and psychiatric distress (Lown et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Parents whose children suffer from cancer describe the importance of support to ease their burden at the beginning of the diagnosis, during treatment, end of treatment, even after completing treatment. Adequate support can help families cope with various crises caused by the disease and its treatment (Björk et al, 2011;Björk et al, 2009;Earle et al, 2007;Sundler et al, 2013). Family, friends and significant others are the sources of support perceived by parents who have children with cancer (Altay et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…30 Some healthy siblings in other studies have also demonstrated avoiding discussing the palliative conditions with their peers or at school due to the fear of not being understood or due to compartmentalisation of school and home. 54,61,62 This is related to the other negative psychological impacts experienced by the healthy siblings as highlighted by the studies included in this review 20,[30][31][32][33][34][36][37][38] which was due to uncertainty about the illness trajectory and in feeling isolated in their illness experience. This was congruent with previous studies on siblings of cancer patients.…”
Section: Discussionmentioning
confidence: 99%